1986
DOI: 10.1002/ejsp.2420160202
|View full text |Cite
|
Sign up to set email alerts
|

The vicissitudes of attitudes and similar representational constructs in twentieth century psychology

Abstract: 'Attitudes' has been the central concept of social psychology in three differentAttitude has been the dominant social psychology concept in three different periods, exercising hegemony over the discipline's imagination for more accrued time than any other concept, even 'groups'. Early commentators as disparate as sociologists Thomas and Znaniecki (1918) and behaviourist J. B. Watson (1925) considered the concept so central that they defined social psychology as the study of attitudes, and Kurt Goldstein (1934… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
7

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(74 citation statements)
references
References 108 publications
(83 reference statements)
2
65
0
7
Order By: Relevance
“…Social-psychological research has demonstrated that societies are capable of creating common belief systems and imparting them to their members (Fraser & Gaskell, 1990;McDougall, 1920;McGuire, 1986;Moscovici, 1988). Furthermore, additional lines of research indicate that societal beliefs and ideologies may be employed in order to justify a group's advantage over others and portray it as legitimate (Jost, Banaji & Nosek, 2004;Sidanius & Pratto, 1999).…”
Section: The Israeli Occupationmentioning
confidence: 99%
“…Social-psychological research has demonstrated that societies are capable of creating common belief systems and imparting them to their members (Fraser & Gaskell, 1990;McDougall, 1920;McGuire, 1986;Moscovici, 1988). Furthermore, additional lines of research indicate that societal beliefs and ideologies may be employed in order to justify a group's advantage over others and portray it as legitimate (Jost, Banaji & Nosek, 2004;Sidanius & Pratto, 1999).…”
Section: The Israeli Occupationmentioning
confidence: 99%
“…One can also list and analyze conceptual distinctions that have been drawn by different researchers, e.g. McGuire's (1986) analysis of six quite varied characteristics that have been proposed to determine when social cognition or social representations are indeed social.…”
Section: F Multiplying Insights By Conceptual Divisionmentioning
confidence: 99%
“…These writers anticipated the socially constituted nature of historical reality and were among the first to address the nature of the relationship between the individual and society, especially the ways in which individual representations and collective representations are dialecti-. cally intertwined (e.g., Gergen, 1998;McGuire, 1986;Moscovici, 1988). In this sense, then, the intellectual origins of experimental social psychology and social constructionism are essentially the same.…”
Section: Social Constructionism As History Common Originsmentioning
confidence: 99%
“…Decades of social psychological research painstakingly document, in fact, that social and cognitive factors typically outside of the individual's control determine which beliefs and arguments they find persuasive (cf. Cialdini, 1988;Eagly & Chailcen, 1993;McGuire, 1986).…”
Section: The Issue Of Truth How Wide Is the Rift?mentioning
confidence: 99%